1999
DOI: 10.1152/ajpregu.1999.276.4.r1118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adrenomedullin and PAMP on adrenal catecholamine release in dogs

Abstract: We examined the effects of proadrenomedullin-derived peptides on the release of adrenal catecholamines in response to cholinergic stimuli in pentobarbital sodium-anesthetized dogs. Drugs were administered into the adrenal gland through the phrenicoabdominal artery. Splanchnic nerve stimulation (1, 2, and 3 Hz) and ACh injection (0.75, 1.5, and 3 μg) produced frequency- or dose-dependent increases in adrenal catecholamine output. These responses were unaffected by infusion of adrenomedullin (1, 3, and 10 ng ⋅ k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…PAMP20 appears to inhibit Ca 2 -dependent, agonist-stimulated catecholamine secretion, acting via specific receptors and through a mechanism involving the impairment of Ca 2 influx in humans. An inhibitory effect of PAMP20 on nicotinic receptor activated catecholamine release has also been observed in in vivo experiments using dogs (55). Catecholamine overflow from the adrenal gland caused by splanchnic nerve stimulation or by acetylcholine injection was suppressed by PAMP20.…”
Section: Functions Of Am Pamp20 and Pamp12 Inmentioning
confidence: 61%
See 1 more Smart Citation
“…PAMP20 appears to inhibit Ca 2 -dependent, agonist-stimulated catecholamine secretion, acting via specific receptors and through a mechanism involving the impairment of Ca 2 influx in humans. An inhibitory effect of PAMP20 on nicotinic receptor activated catecholamine release has also been observed in in vivo experiments using dogs (55). Catecholamine overflow from the adrenal gland caused by splanchnic nerve stimulation or by acetylcholine injection was suppressed by PAMP20.…”
Section: Functions Of Am Pamp20 and Pamp12 Inmentioning
confidence: 61%
“…In addition, neither AM nor AM had any effect on either basal catecholamine release, catecholamine release induced by electrical stimulation of the splanchnic nerve, or catecholamine release induced by acetylcholine injection into the phrenico-abdominal artery of dogs, indicating that AM does not play a significant role in the regulated exocytosis of catecholamine in adrenal chromaffin cells (55).…”
Section: Functions Of Am Pamp20 and Pamp12 Inmentioning
confidence: 78%
“…Masada et al [38] have investigated the effects of ADM and PAMP on the release of adrenal catecholamines in response to cholinergic stimuli in pentobarbital sodium-anesthetized dogs. They reported that PAMP, but not ADM, can act as an inhibitory regulator of adrenal catecholamine release.…”
Section: Discussionmentioning
confidence: 99%
“…The data suggesting that adrenomedullin interacts with the CGRP receptor are derived mainly from functional studies. It is difficult to carry out similar studies on the adrenal medulla as adrenomedullin does not appear to affect catecholamine release in bovine chromaffin cells (Houchi et al, 1996), intact dogs (Masada et al, 1999), or rat adrenal tissue (Kapas et al, 1998). It remains possible, however, that the adrenomedullin gene product, PAMP, may influence chromaffin cell function.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that adrenomedullin is able to influence adrenal medullary function. Although no direct effect of adrenomedullin on catecholamine release has been demonstrated in rat adrenal glands (Kapas et al, 1998), dogs (Masada et al, 1999), or bovine chromaffin cells (Houchi et al, 1996), adrenomedullin stimulates calcium efflux from cultured chromaffin cells (Houchi et al, 1996).…”
mentioning
confidence: 99%